Teologia em perspectiva afrodiaspórica e antirracista : uma análise do potencial correlativo entre a teoria decolonial e a teologia negra da libertação - Andrade, Charlisson Silva de (2020)
Black Liberation Theology, systematized in the mid twentieth century, is based on the aphrodiasporic experience in the Americas and in the context of protest against white colonial rule in Africa. Guided by the principles of Liberation and Justice, this theological perspective correlates the Christian message with the historical-cultural situation in which it is inserted, aiming at a concrete transformation in history, by engaging in the anti-racist struggle. From the observation of the black theological criticism to the supposed universality of western Euro theology, our general objective is to analyze the correlative potential between decolonial theory and Black Liberation Theology, considering the historical situations that condition the hermeneutics of both, especially with regard to the relationship between modernity, religion and coloniality. To carry out the analysis, we used authors such as Paul Tillich and Claude Geffré, with regard to the understanding of the theorists mentioned about the hermeneutic condition of theology, synthesized in the "method of correlation" and in the conception of “hermeneutic turn”, respectively. At first, we draw a panorama of Black Liberation Theology, in the United States and in Brazil, highlighting the correlational constitution between theology and “situation”, identifying the hermeneutics involved in this theology, radicalized in the affirmation of the theological subject's body as a condition without which there is no theological hermeneutics, and the fight against racism as its starting point. Then, we identify the main critical and propositional arguments of decolonial theory in its hermeneutics engaged against Eurocentrism, which, when understanding coloniality as constitutive of modernity, and not derivative of it, suggests the epistemic reconstitution of subalternized peoples. From this, we analyze the correlation between decolonial theory and aphrodiasporic intellectual production and the possible place of theology in the decolonial project, appropriating a criterion established by decolonial theorists, in which the articulation between social place and epistemic place is essential for the formulation of a counter-hegemonic discourse committed to the oppressed people. Finally, we analyze the correlative potential between decolonial theory and Black Liberation Theology. After having addressed the hermeneutics of modernity carried out by decolonial theorists and identifying the presence of their perspective in black theological hermeneutics and their theological answer to the questions implicit in the “situation”, privileging the analysis of the book God of the Oppressed, by James Cone, we were able to state Black Liberation Theology as an aphrodiasporic, anti-racist and decolonial theology.